Stigmatization of people with psoriasis - Ogłodek, Ewa; Araszkiewicz, Aleksander; Placek, Waldemar (Polish Journal of Public Health, 2009)
Psychodermatologic disorders are conditions involving an interaction between the skin and the mind. Understanding the psychosocial and occupational context of skin diseases is critical for the optimal management of psychodermatological disorders. The problem of social stigmatization is characterized in the paper. Psoriasis is a chronic, recurrent, inflammatory disease, which affects 1-3% of the population. In the course of the disease skin lesions are often extensive and causing disfiguring of the patients. Psoriasis can be regarded socially excluding stigmata. Stigmatization is a common problem to overcome for people suffering from chronic diseases. The basic theoretical assumptions of the stigmatization are presented in the paper. Stigmatization can be recognized if there is a concurrence of labeling, stereotypy, exclusion, emotional reactions, loss of social status and discriminations. Stigmatization accompanies patients all the time, influences their families, social and occupational life. Social stigmatization and discrimination of person with psoriasis is a common problem. The presence of chronic disease and associated visible skin changes significantly affect the psychosocial functioning of patients, and contribute to reducing social contacts and the deterioration of social and living conditions. We are still looking for new therapies that could reduce the tremendous negative impact on the mental state of psoriasis patients. Taking into account the social context of psoriasis is essential to effective treatment.